The Interplay of Religious Festivals Diwali and Eid in Shaping National and Ethnic Identity Concepts of the Indian Society - Dadman, Enayatullah; Patel, Anjali (International Journal of Contemporary Sciences (IJCS), 2024)
This study explores the interplay of religious festivals, specifically Diwali and Eid, in shaping national and ethnic identity concepts within Indian society. The objective of this research was to analyse how Diwali, predominantly celebrated by Hindus, and Eid, central to the Muslim community, contribute to both national unity and ethnic distinctiveness in India. Using a qualitative comparative study approach, archival research and media content analysis were conducted to examine the broader socio-political narratives surrounding these festivals. Findings revealed that Diwali is closely tied to the construction of Hindu identity and is often intertwined with Indian national identity, promoting a sense of unity. Eid, on the other hand, reinforced ethnic and religious identity among Muslims, fostering community cohesion while simultaneously highlighting the complexities of belonging within the larger national framework. The study concludes that both Diwali and Eid play critical yet contrasting roles in shaping India’s multi-layered identity, with Diwali promoting a homogenizing national identity and Eid emphasizing religious distinctiveness.